Impulse Buying: A Multi-National Consumer Study - Yukta Malani; Srihitha Aakula; Zaker Ul Oman (Involvement International Journal of Business, 2024)
This study explores impulsive buying behavior among consumers in India and other countries. It identifies factors influencing impulsive purchases, analyses the most impulsively bought product categories, and explores the post-purchase satisfaction of these impulsive decisions. Additionally, the study examines the personality traits of impulsive buyers compared to non-impulsive buyers. The research highlights the factors marketers and retailers can leverage to encourage impulsive purchases. It also empowers consumers to identify their impulsive buying tendencies and understand the emotional drivers behind them. The study provides valuable insights for entrepreneurs, marketers, retailers, and consumers.